Contextual Factors Associated with the 30-15 Intermittent Fitness Test in a Youth Football Academy - Gonzalo Fernández Jávega; Iván Peña-González (Asociación Española de Ciencias del Deporte, 2024)
The aim of this study was to examine the effect of various contextual factors on the 30-15 Intermittent Fitness Test (30-15 IFT) in young male football players.30-15 IFT was evaluated in U-14 and U-16 football teams (n=229). The sample was categorized by relative age, biological maturation, playing position and competitive level (CL). The results revealed a trend in the overall sample towards an overrepresentation of players born in the early months of the year. Significant differences were found when comparing vIFT (maximal intermittent running velocity) values across age categories (U13: 17.73 ± 1.24; U14: 18.14 ± 1.56; U15: 18.99 ± 1.31; U16: 18.81 ± 1.55; F = 9.93; p < .001) and between maturity groups, in favor of the more mature players (PrePHV: 17.77 ± 1.38; MidPHV: 18.53 ± 1.37; PostPHV: 18.83 ± 1.48). There were some minor differences in the vIFT between players from different field positions (F = 2.96; p = .014; ηp2 = 0.078). As well as players who compete at higher levels of competition reached higher results for the vIFT (CL: F = 9.01; p < .001; ηp2 = 0.238 and CL2: F = 15.44; p < .001; ηp2 = 0.184). This study showed the complexity of factors influencing the 30-15 IFT of young football players and suggest that maturity may play a more influential role than RA in physical performance which could influence the selection process at early ages.